Fabrication of Ultrathin Bi2S3 Nanosheets for High‐Performance, Flexible, Visible–NIR Photodetectors. Issue 24 (19th February 2015) - Chen, Guihuan; Yu, Yongqiang; Zheng, Kun; Ding, Tao; Wang, Wenliang; Jiang, Yang; Yang, Qing
<x xml:space="preserve">Abstract</x> Ultrathin Bi2S3 nanosheets with thicknesses down to 2.2 nm are fabricated. The resultant ultrathin Bi2S3‐based photoconductor shows high sensitivity to visible–near infrared light from 405 to 780 nm with a high external photoresponsivity up to 4.4 A W−1, high detectivity of ≈1011 Jones, relatively fast response time of ≈10 μs, and high flexibility and durability.